THE IMPACT OF SMALL AND MEDIUM ENTERPRISES INCOME ON WELFARE IN THE PERSPECTIVE OF SHARIA ECONOMY - Amiruddin Kadir (ITB AAS Indonesia Surakarta, 2024)
This study aims to find out the following: (1) To find out the income of Emping Melinjo Small and Medium Enterprise workers in Kohala Village, Benteng District, Selayar Regency, (2) To find out how the impact of Islamic welfare of workers on family income in Emping Melinjo Small and Medium Enterprises (SMEs) in Kohala Village, Benteng District, Selayar Regency, (3) To find out how the implementation of wages (Al-Ujrah) according to the perspective of Islamic economics. This research shows that with the existence of Small and Medium Enterprises emping melinjo, workers can help the family economy and have a positive impact that can be felt from some communities even though there are some of them who do not get their rights precisely as discussed in the Islamic economic perspective about the obligation to pay wages (Al-Ujrah) workers before their sweat is dry, but when viewed from the welfare of the community, This business cannot be fully said to be prosperous because the income earned by workers is still below the standard of the Provincial Minimum Wage (Al-Ujrah) (UMP).